Organic biomass – alternative energy source - Seryogin, Oleksandr; Osmak, Alexei (My University, 2013)
Наведено перспективу виробництва синтез-газу шляхом термічної конверсії органічної сировини. Описано принцип роботи газогенератора для спалювання рослинної біомаси. Shows the prospect of producing synthesis gas by thermal conversion of organic materials. We describe the principle of the gasifier for biomass burning.
Keywords: органічна біомаса; organic biomass; газогенератор; gas-producer; синтез-газ; synthesis gas; кафедра електропостачання і енергоменеджменту